APPLYING MULTIPLE INTELLIGENCESIN TEACHING ENGLISH TO YOUNG LEARNERS(A DESCRIPTIVE STUDY AT TK PONDOK ANAK PINTAR, CIMAHI) - Elroy, - (2008)
This paper is entitled Applying Multiple Intelligences in Teaching English to Young Learners (A Descriptive Study at TK Pondok Anak Pintar, Cimahi). The aims of this study is to find out teacher's knowledge about multiple intelligences, the activities referring to multiple intelligences applied in the classroom, how the teacher implemented multiple intelligences in teaching English to young learners, and the difficulties faced in implementing multiple intelligences in teaching English to young learners. The data were obtained from observation, interview, questionnaire, and documents. There is no treatment during the research as this study employs descriptive qualitative method. After collecting the data, they were analyzed using Miles and Huberman model - data reduction, data display, and conclusion. Based on the findings, the teacher may have a good knowledge of multiple intelligences theory based on the questionnaire. Moreover, she created various activities to support the development of the students' intelligences. However, the teacher found some difficulties in creating activities that were suitable for the development of students' intelligence. Though the teacher has a good knowledge of the theories, it does not mean that it is enough. Teacher still has to update her knowledge often so the students' intelligences could be developed well. To conclude, teacher has to facilitate the students' development by giving suitable activities go with their dominant intelligences - the strongest intelligence that students possess.